2021
DOI: 10.3390/foods10081934
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety of Consuming Black Soldier Fly (Hermetia illucens) Larvae: Microbial, Heavy Metal and Cross-Reactive Allergen Risks

Abstract: Black soldier fly (Hermetia illucens) larvae (BSFL) are a promising, sustainable source of nutrients, however, there is limited knowledge regarding the food safety of consuming BSFL. This study determined the safety of consuming BSFL for direct human consumption in terms of microbial, heavy metal and allergen content. Microbial counts were determined using ISO (International Organization for Standardization) methods, heavy metals were determined using inductively coupled plasma mass spectrometry and allergens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 55 publications
(145 reference statements)
3
40
0
Order By: Relevance
“…This may explain the higher Mo and B concentrations in the smaller scale where the larvae were significantly smaller. Nevertheless, the factors that influence the accumulation of micro and macro elements in the larvae is a topic for future research due to their importance for the production of larvae with a higher nutritional value and enhanced safety [65]. The differences observed in this study point out the need for developing industrial larvae harvesting methods that enable the separation of larvae before fully consuming or drying the substrate.…”
Section: Discussionmentioning
confidence: 91%
“…This may explain the higher Mo and B concentrations in the smaller scale where the larvae were significantly smaller. Nevertheless, the factors that influence the accumulation of micro and macro elements in the larvae is a topic for future research due to their importance for the production of larvae with a higher nutritional value and enhanced safety [65]. The differences observed in this study point out the need for developing industrial larvae harvesting methods that enable the separation of larvae before fully consuming or drying the substrate.…”
Section: Discussionmentioning
confidence: 91%
“…Analysis of some larval extracts by Dong et al ( 28 ) found lauric acid and medium-chain fatty acid derivatives in high concentrations with antimicrobial effects against Gram-positive bacteria ( 28 ). Additionally, factors like pH and the enzymatic reactions of the BSFL gut are believed to reduce bacterial populations ( 29 , 30 ). Characterization of antimicrobial peptides, such as the defensin-like peptides, found in BSFL have proven antibacterial effects on both Gram-positive and Gram-negative bacteria ( 29 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae are currently fed vegetable, dairy, and bakery byproducts, spent brewers' or distillers' grains, and animal feeds, with short-term plans to expand into food surplus and animal by-products. Long-term plans for BSF propose feeding them manure, municipal waste, and slaughterhouse, meat, or fish waste, though these may present safety concerns for organisms consuming the final BSF as a product (Bessa et al, 2021;EFSA, 2015;FAO, 2021).…”
Section: Larval Rearing Practicesmentioning
confidence: 99%
“…Finally, selective breeding for particular life-history traits (such as fast development, or high fecundity) may result in genetic bottlenecks, inbreeding depression, and potentially colony collapse due to reductions in stress resistance and longevity (Gilchrist et al, 2012); colonies should be carefully managed to maintain genetic diversity, and thus healthier populations (Hoffman et al, 2021;Rhode et al, 2020).…”
Section: Genetic Modification and Selective Breedingmentioning
confidence: 99%